Signal processing challenges in active queue management. - Bohacek, S. (IEEE Signal processing magazine)
The publication of Floyd and Jacobson's seminal paper "Random early detection gateways for congestion avoidance" (1993), marked a new direction in networking research and began what is perhaps the most investigated example of cross-layer optimization. While this paper has inspired an immense amount of work in research, many open problems in active queue management (AQM) still remain. This article seeks to frame these problems in terms accessible to the signal processing researchers. The basic idea of AQM has been provided as well as its objective and overviews of a sample of different approaches. The signal processing aspects of the AQM are discussed, specifically the problem of predicting congestion, approaches to detecting changes in network traffic, an estimation problem, dithering, and quantization.